Using Social Work Interventions to Address Climate and Disaster Risks in Latin America and the Caribbean - Vivanco M., Lucía; Villagrán A., Andrea; Martínez R., Víctor (World Bank, Washington, DC, 2020)
Disasters associated with adverse natural events are increasing in both frequency and intensity, and in many cases, have severe impacts on countries and their populations, particularly those living in poverty and in socially vulnerable situations. Poor or limited access to both material and immaterial resources hinders the ability of these populations to confront the damages and losses caused by disasters, and thereby restore their material and psychosocial well-being in a timely and effective manner. This note is particularly concerned with guiding countries in the design and implementation of methodologies typically used in Social Work, such as family support, case management, and other interventions, in disaster contexts in order to contribute to the construction of Adaptive Social Protection (ASP) systems. Social Work strategies can be employed within ASP systems to help identify and reduce risks, determine appropriate responses, and support strengthening the resilience of affected individuals and families.